Antimicrobial Bacterial Cellulose-Silver Nanoparticles Composite Membranes - Barud, Hernane S. [UNESP]; Regiani, Thais [UNESP]; Marques, Rodrigo Fernando Costa [UNESP]; Lustri, Wilton R.; Messaddeq, Younes [UNESP]; Ribeiro, Sidney José Lima [UNESP] (Hindawi Publishing Corporation, 2011)
Antimicrobial bacterial cellulose-silver nanoparticles composite membranes have been obtained by in situ preparation of Ag nanoparticles from hydrolytic decomposition of silver nitrate solution using triethanolamine as reducing and complexing agent. The formation of silver nanoparticles was evidenced by the X-ray diffraction, scanning electron microscopy (SEM), transmission electron microscopy (TEM), and absorption in the UV-Visible (350nm to 600 nm). Thermal and mechanical properties together with swelling behavior for water were considered. TEA concentration was observed to be important in order to obtain only Ag particles and not a mixture of silver oxides. It was also observed to control particle size and amount of silver contents in bacterial cellulose. The composite membranes exhibited strong antimicrobial activity against Gram-negative and Gram-positive bacteria.